Analysis of Early Marriage in Jember Regency from the Perspective of Islamic Law and Positive Law in Indonesia - Divani Aina Nurlita; Faizyah Artika Harani; Lubabin Nawval Muhammad; Much. Ircham Faridil Kudsi; Imelia Rossa Najwa Anastassya (Indonesian Journal of Islamic Religion and Culture, 2024)
This research examines the phenomenon of early marriage from the perspectives of Islamic law and positive law in Indonesia. The methodology employed includes an empirical approach involving direct observation, in-depth interviews, and a literature review. Interviews were conducted using Google Forms, with participants aged 18–21 years serving as the subjects. The results reveal diverse public views on early marriage: some consider it a tradition that should be respected, while others view it as a violation of human rights. Economic, cultural, and educational factors were identified as the primary drivers of the high rate of early marriage in Jember Regency. A legal analysis indicates that, while Islamic law permits early marriage based on the attainment of puberty, Indonesian positive law stipulates a minimum age for marriage. The study concludes that misunderstandings about Islamic law and a lack of education are significant contributors to early marriage in Indonesia. The author recommends increasing public education and enforcing stricter legal regulations to reduce the prevalence of early marriages.